An eventful course of a routine laparoscopic appendectomy: case report - Khalifa, Aiden; Devanabanda, Bhavana; Louis, Martine (International Surgery Journal, 2020)
Acute appendicitis is one of the most common surgical emergencies in the world. Appendectomy can be done through an open technique, but the laparoscopic approach has become the gold standard for surgical treatment of acute appendicitis. This technique has been found to be associated with decreased postoperative pain, morbidity and length of stay when compared to open appendectomy. However, complications from laparoscopic appendectomy can still occur. We present a case of an internal hernia causing a small bowel obstruction, from adhesions due to loose staples after a laparoscopic appendectomy. Laparoscopic linear cutting staples and automatic clip applier are commonly fired across the appendiceal stump. At the end of the laparoscopy, if the free intraperitoneal staples are not removed with grasper or suction, it can lead to bowel obstruction. We report the clinical presentation, diagnostic work up, treatment and management of mechanical small bowel obstruction caused by loose staples in a pediatric patient.